Retiring from driving and riding: Be safe and not a risk. (September 2020) - Ang, Boon Hong; Huey Lee, Shaun Wen; Chen, Won Sun; Yap, Khai Khun; Song, Keang Peng; Oxley, Jennifer Anne
Abstract: Introduction: Much of the research on transportation and safe mobility focuses on older adult's thoughts and feelings on driving transition in high-income countries, but there is limited knowledge on this process and its consequences in low-and-middle-income countries. Moreover, there is very little understanding of the transition process involving other forms of transport, specifically the motorcycle. This study aimed to understand the process of driving/riding cessation involving former car drivers and former motorcycle riders, including the motivations that act as driving forces influencing the decision to cease driving/riding, challenges faced during the transition, and strategies adopted to adjust to life without driving/riding. Methods: Older Malaysian adults aged 60 years and above who had ceased driving and/or riding were interviewed and responded to questions relating to their decision to stop driving/riding. All interview responses were transcribed verbatim and examined using a thematic approach to identify the factors contributing to this decision. Results: Five themes and 16 sub-themes were identified: [1] being a driver/rider; [2] making the adjustment; [3] making the decision; [4] experiencing multiple losses; and, [5] coping with transition. Physical, psychological, and social factors were important contributors to driving/riding cessation. Motorcycle riders were at higher risk of road crash and ceased more readily than car drivers. Renewing license, transitioning from riding to driving, and utilising multiple alternative means of transportation were unique coping strategies adopted during post-cessation phase. Conclusions: The current findings suggest that cessation is a transition outcome of self-regulation and a successful transition requires discovery of safer mobility opportunities beyond driving and riding. These findings provide direction for the development of culturally sensitive policy and interventions by taking into consideration travel mode preferences and distribution in countries with mixed travel modes to assist retiring car drivers and motorcycle riders to maintain mobility and access in safety. Highlights: A pioneering study describing older motorcycle riders' experiences in riding cessation. Motorcycle riders were at higher risk of road crash and ceased riding more readily than car drivers. Renewing license was a coping strategy contributing to self-identity and emotional adjustment. Dual-mode road users reduced crash risk by transitioning from riding to driving. Combined transportation was a form of self-regulation of driving for dual-mode road users.